Faktor-Faktor yang Mempengaruhi Tingkat Kesejahteraan Keluarga - Rini Astika; La Harudu; Surdin (Jurnal Penelitian Pendidikan Geografi, 2023)
National development is very dependent on family life which is the core part of society. The family has strategic value in national development and is the foundation for holistic human development. This research aims to: 1) determine the level of family welfare in Watumerembe Village; and 2) to determine the factors that influence the welfare of Watumerembe Village families. This type of research is descriptive with a survey method via interviews. The research results show: 1) the level of family welfare in Watumerembe Village is at the KS I welfare stage, namely 23 families (57.50%), KS II has 14 families (35%), KS III has 2 families (5.00 %), and for KS III Plus there is 1 (2.50%). This indicates that the Watumerembe Village family has been able to fulfill the family's basic needs; 2) factors that influence family welfare in Watumerembe Village are economic conditions (income or income), social conditions (education, occupation and health of patriarch), living conditions, and number/size of family.